Sex differences in prenatal programming of hypertension by dexamethasone. Issue 13 (July 2021) - Alhamoud, Issa; Legan, Susan K; Gattineni, Jyothsna; Baum, Michel
Prenatal dexamethasone has been shown to increase blood pressure in male offspring but the mechanism for the increase in blood pressure is unclear. The present study examined if prenatal programming by maternal injection of dexamethasone on days 15 and 16 of gestation affected the blood pressure comparably in female and male offspring. Our hypothesis was that males would be affected by prenatal dexamethasone to a greater extent than females and that either an increase in renal tubular transporter abundance or an increase in renin or aldosterone system would be associated with hypertension with prenatal programming. Prenatal dexamethasone increased blood pressure at two months and six months of age and resulted in proteinuria and albuminuria at six months in male but not female rat offspring. There was no effect of prenatal dexamethasone on blood pressure and proteinuria at one month in male and in female offspring. While prenatal dexamethasone increased male renal thick ascending limb sodium potassium two chloride cotransporter protein abundance at two months, prenatal dexamethasone on days 15 and 16 of gestation did not affect transporter abundance in males at other ages, nor did it affect proximal tubule sodium/hydrogen exchanger or distal convoluted tubule sodium chloride cotransporter protein abundance at any age. There was no difference in systemic renin or aldosterone in the prenatal dexamethasone group compared to same sex controls. In conclusion, male but not female offspring have an increase in blood pressure and urinary protein excretion with prenatal dexamethasone. The increase in blood pressure with prenatal programming was not associated with a consistent increase in renal tubular transporter protein abundance, nor plasma renin activity and serum aldosterone.